Baba Babnega polja - Pleterski, Andrej (Array, 2012)
According to local tradition, a huge Baba (hag, woman) lies in the Bohinj valley in northwest Slovenia, geographically dividing Bohinj into its upper and its lower valley. Familiar with this tradition, the authors of this essay decided to ascertain to what degree, if so at all, the circumstances in Babno polje (fi eld of Baba ; south Slovenia on the border with Croatia) resemble the ones in Bohinj. Do old traditions indicating the perception of Mokoš among ancient Slavs still exist, and what are their possible connections with the term Babno polje? In order to provide the answer to the preliminary question it is possible to say that an analysis of folk tradition, written sources, and archaeological data indicates that the origin of the term Babno polje is in the somewhat unexpected – and as yet unconsidered – source of the stream Trbuhovica (the related term trebuh denotes stomach), respectively in Baba lying in the valley. Within this particular context, the oronym Otročji Hrib (Child’s Hill) acquires the meaning of a part of Baba’s body (as well as Trbuhovica). It may be possible to include in this context a hill Šmarni Grič (also named Šmarna Gora), and possibly even the entire village of Babna Polica in the vicinity. While the prostrate body of Baba is clearly discernible in Bohinj this has yet not been established for Babno Polje. However, the childbearing part of the afore-mentioned Baba, the spring Trbuhovica, is quite unambiguous. Th e two topographic pairs, namely Miklavževa Lokvica and Šmarni Grič in the northwest and Trbuhovica and Marija Sedem Žalosti in the southeast, which are situated opposite each other and form the borders to Babno polje, possibly indicate the dual nature of Baba (Mokoš). While the southern part of this extensive fi eld is interspersed with water sources (there are several others in addition to Trbuhovica) its northern counterpart is quite arid. Vražji Vrtec, a local hill with the grave of Ali-Paša, doubtlessly played a role in connection with the cultic perception of the yearly cycle of nature ; however, this is a subject that will have to be discussed in a separate article. Turkish raids and Christianization have totally mixed and blurred the original mythical landscape. Yet it may be possible to discover its secrets in the future, and also explore the relation between Baba and Mokoš, who are clearly not just simply identical. Topographically three areas of mythic events are suggested in Babno polje region: birth from Trbuhovica, marriage (Vragofk a and Vražji vrtec), death (Miklavževa lokvica).